Gangguan fisiologi dan biokimia Crocidolomia pavonana (F.) (Lepidoptera: Crambidae) akibat perlakuan ekstrak campuran Tephrosia vogelli dan Piper aduncum - Eka Chandra Lina; Dadang Dadang; Syafrida Manuwoto; Gustini Syahbirin (Perhimpunan Entomologi Indonesia, 2015)
Plant extracts have been known to cause physiological and biochemical interferences against insect, such as feeding inhibitor, food assimilation, and changes on activity of cytochrome b5 and cytochrome P450. This study was carried out to examine the effect of the extracts mixture of Tephrosia vogeliiand : Piper aduncum (1 : 5) on the physiology of Crocidolomia pavonana (F.) as well as extract of P. aduncum on biochemical of C. pavonana. The study showed that larvae of C. pavonana was experiencing a feeding inhibition until 94.82% after treated with extracts mixture on concentration 0.06% or equivalent to LC95. However, larvae treated with extracts mixture on LC25 and LC50 only experienced a relative growth disorders as a result of intrinsic toxicity of extracts mixture which enters into the body of insects. Insect adaptation to toxic plant compounds indicated by an increase in the digestibility of larvae approximately 11.11%. Furthermore, detoxification mechanism by larvae against active compounds of P. aduncum occured and shown by an increase of oxidative enzyme activity of cytochrome b5 and cytochrome P450, in in vivo and in vitro compared to control. This study provides an information about mode of action of extracts mixture of T. vogelii and P. aduncum (1 : 5) on larvae of C. pavonana and detoxification mechanism by larvae due to extract of P. aduncum